PERSONAL RESPONSE TO DISEASE IN PARAFUNCTIONS OF MASTICATORY MUSCLES - A. K. Iordanishvili; A. A. Serikov; A. R. Faizov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Particularities of personality of a sick person play an important role in providing effective treatment and prevention of relapse in various pathologies. Therefore, the position of the patient in relation to his/her health and ongoing treatment, as well as to doctors and auxiliary medical personnel are important factors in the success of rehabilitation.Parafunctions of masticatory muscles, which are understood as an impractical inappropriate activity, are known to be often found. They are poorly amenable to treatment and very painful for patients. The use of psychopharmaceutical and psychotherapeutic methods aimed at changing the patient’s attitude to the disease can help to cure such dental patient. This can change the patient’s response to the disease and create realistic settings for treatment. At the same time, the study of the attitude of dental patients to the disease is practically not covered in the accessible domestic and foreign literature. The purpose of study is researchthe attitude to the disease of adults suffering from various forms of parafunctions of the masticatory muscles.Material and methods. The work was carried out to study the attitude of 29 adults suffering from various forms of parafunctions of the masticatory muscles to the disease. To determine the type of attitude to the patient’s disease,we used the TOBOL clinical test method (type of attitude to the disease), which implements the clinical and psychological typology of patient attitude and provides for the possibility of defining one of the twelve types of responses.Results. It was found that before treatment, regardless of age in individuals suffering from parafunction of the masticatory muscles,there were more common types of attitude to the disease, in which the observed maladaptive behavior with predominantly intrapsychic oriented response to the disease manifested the characteristic reactions of the type of irritable weakness, anxiety, depressed and oppressed condition. The performed complex treatment with the use of complex dental treatment and preventive measures, physical therapy exercises and antispasmodic of skeletal muscles allowed to achieve treatment efficiency of 95.8 %. Thus, it changed patients’ inadequate response to the disease, eliminated significant signs of mental maladjustment, as well as createdrealistic attitude to treatmentin patients, helped to restore broad social relations and active participation in treatment.Conclusions. The obtained data about the type of attitude of patients with such chronic, severe and painful pathology as parafunct ions of masticatory muscles are of practical value, as the achievement of a positive therapeutic result and successful rehabilitation are possible only if the patient’s attitude toward the disease changes, especially in the second and third types in the framework of the test «Type of attitude towards the disease» (TOBOL), therefore the involvement of a clinical pharmacologist or psychiatrist is necessary for rehabilitation of such patients.